Thermodynamic analysis of vapor compression cycle with oil flooding from intermediate pressure port. (25th February 2018) - Liu, Qi; Yuan, Zhipeng; Luo, Baojun; Li, Zhenming; Fu, Jianqin; Chen, Jingwei
Highlights: Intermediate pressure oil injection port is proposed for oil flooded compression. The modification has a beneficial effect on COPc and cooling capacity. Coefficient of oil absorbed heat in the compression process is defined and obtained. Performance improvements of the systems are different for R410A and R32. Abstract: Oil flooded compression is able to improve the performance of vapor compression cycle by approaching a quasi-isothermal compression process. In conventional Oil Flooded Compression Cycle (OFCC), oil is usually injected in the compression chambers just after the compression pockets are sealed off from the suction chambers. In this research, OFCC with intermediate pressure port (OFCC-IPP) is proposed. The performance characteristics of OFCC-IPP with and without regenerator using R410A and R32 working fluids are investigated and compared to conventional OFCC with and without regenerator. Theoretical results show that the improvement of ratios of COPc and cooling capacity in the OFCC-IPP systems can be up to 4.5% an 5.3% respectively compared to the OFCC systems under the operating conditions of 40 °C condensing temperature and evaporating temperature in the range of −25 °C and 5 °C. Besides, the performance improvements of the OFCC and OFCC-IPP systems are different for the R410A and R32 working fluids. The results suggest that OFCC-IPP has huge potential for applications as an alternative to the conventional OFCC.